1981
DOI: 10.1073/pnas.78.12.7360
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural identification of extension aminopropeptides of type I and III collagens in human skin.

Abstract: Human skin was labeled with purified antibodies against type I and m collagens and against their extension aminopropeptides by using the ferritin technique. Both aminopropeptides were visualized mainly along thin collagenous fibrils (diameter, 20-40 nm) and rarely in nonfibrillar regions of the skin. The labeling showed a periodicity of 60-65 nm resembling the D (67 nm) stagger of collagen molecules. Blocking of antibodies with aminopropeptides and treatment of tissues with procollagen NH2-terminal protease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(87 citation statements)
references
References 31 publications
7
80
0
Order By: Relevance
“…In accordance with previous studies [9,44,29], type III collagen and hyaluronic acid stained intensely in the normal subpapillary connective tissue surrounding the haemangidmas and in the connective tissue matrix between the capillary loops. In contrast to this, staining for type III collagen was very weak in the thickened vascular wall of the haemangioma capillaries; in these areas there were also ultrastructurally only a few scattered collagen fibrils with a periodicity of 67 nm.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies [9,44,29], type III collagen and hyaluronic acid stained intensely in the normal subpapillary connective tissue surrounding the haemangidmas and in the connective tissue matrix between the capillary loops. In contrast to this, staining for type III collagen was very weak in the thickened vascular wall of the haemangioma capillaries; in these areas there were also ultrastructurally only a few scattered collagen fibrils with a periodicity of 67 nm.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the duration of the so-called 'lag (or nucleation) phase' of fibril growth, which is altered by the presence of different GAGS, would directly affect the number-density of collagen fibrils so formed, in that collagen fibrils of smaller diameters would be produced when the nucleation phase was long and those of larger diameters when the nucleation phase was short [7][8][9]131. However, other experiments have shown that collagen molecules are capable of aggregating into fibrils in the absence of any of the GAGS [4,7,11] and that fibril diameter may be dependent upon glycoprotein content [ 141, parameters such as pH, ionic strength and temperature [3,, the distribution and number of glycosylated residues along the length of the collagen molecule [ 191, the degree of copolymerisation in some tissues of types I and III collagen , collagen-fibronectin interactions [22] and the amount of collagen extension aminopropeptides remaining in the fibril [23].…”
mentioning
confidence: 99%
“…They are liberated during the conversion of the precursor into collagen [1,2] and are considered to play important roles in regulating collagen synthesis [3] and fibril formation [4,5]. The amino acid sequence of the aminopropeptides of procollagen I and 111 has been elucidated [2, 6,7] supporting previous evidence on three structurally and conformationally distinct domains [8 -101 in each peptide segment.…”
mentioning
confidence: 82%
“…Similar data are still lacking for the homologous segment of procollagen 111. However, antibodies against this peptide have been of value for studying its matrix function [4] and for developing sensitive radioimmunoassays for quantifying circulating antigens under clinical conditions [I 71. The latter approach indicated different affinities for the intact aminopropeptide and smaller antigenic fra'gments which may arise in the body due to physiologic dcgradation [I 7 -191.…”
mentioning
confidence: 99%